Ответы и объяснения

2013-07-10T21:16:09+04:00

2а+2в                1                   1                     2*(а+в)            (а+в)-(а-в)           2                 а+в-а+в

-------------  *  (  --------- --    -------------) = ---------------- *   ------------------ = ----------- * --------------  =     

      в                 а-в                     а+в                   в                 (а-в)*(а+в)               в              (а-в)

 

 2                2в                4

-------- * ------------ = ------------

   в              (а-в)           а-в